Development of smart optical agents for disease theranostics - Zeng, Ziling (Nanyang Technological University, 2024)
For the past decades, tremendous progress has been made in the field of biophotonics with applications in both biomedical research and clinical practice. With the merits of high sensitivity and specificity in real-time biological investigations and increased versatility and multimodality adaptive to diverse research and clinical needs, biophotonics as a powerful and non-invasive tool holds significant potential in disease treatment and diagnostics. Compared to inorganic optical agents, organic optical agents possess superiorities of high biocompatibility and biosafety, structurally tunable properties, and relatively low cost, rendering them attractive candidates for two major biomedical applications of biophotonics: 1) light-activated therapy; 2) optical imaging and diagnosis. Despite the fact that a diverse array of organic optical agents has been exploited in preclinical studies, there is still ample room for improvement and expanded clinical applications, such as lack in a precisely controllable manner, noninvasive, dynamic diagnosis of disease, or monitoring of disease progression. Therefore, our group has dedicated great efforts to overcoming these challenges, improving the performance of activatable optical agents, and expanding their use in various disease models and practical scenarios. This thesis is built with a structure of the following: a comprehensive review emphasizing past studies and current advances in biophotonics for disease treatment and diagnosis. Next, my studies that focused on improving optical agents from the aspects of precise control and extended clinical applications are presented. Specifically, to achieve the precise control of therapeutics, Chapter 3 investigates activatable organic semiconducting polymer nanoparticles (SPNs) for combination photodynamic immunotherapy, in which both photodynamic and immunotherapeutic activities can be controlled by photoirradiation. Based on Chapter 3, Chapter 4 further explores the SPNs as sonosensitizers for activatable sonoimmunotherpy, which overcomes the shallow tissue penetration of light, an inherent limitation of conventional phototherapy. To broaden the clinical applications and enhance the translational potential of activatable optical agents, Chapter 5 investigates a proof-of-concept approach to develop novel inhalable activatable probes, which enable both in vivo NIRF imaging and optical urinalysis allowing non-invasive and real-time detection of SARS-CoV-2. Inspired by this concept, Chapter 6 investigated the use of inhalable probes in longitudinal monitoring of disease progression and treatment outcomes. Finally, considering the rapid progression and great potential of smart optical agents, future perspectives from the aspects of optical agent development and clinical translation are proposed.